“DETERMINANTS OF AUDIT DELAY IN INDONESIA COMPANIES: EMPIRICAL EVIDENCE” - Luki Retno Puri Rahayu (INVENTORY: JURNAL AKUNTANSI, 2017)
AbstractThe purpose of this research is to examine the impact of firm size, DER, auditor opinion, anda public accounting firm sizetoward audit delay in sanctions-hit Indonesia Stock Exchange in 2013.The population of the study is a company that sanctioned the Indonesia Stock Exchange in 2013 and listed on the Indonesian Stock Exchange in the period 2012-2015.These samples wereselected by using Purposive sampling method with the total sample of 16 companies. The data analysis uses multiple regressions. The results showed that the firm size, DER, auditor opinion, and a public accounting firm sizenot affect audit delay. Partial testing, showing the firm size, DER, auditor opinion, and a public accounting firm sizenot affect audit delay.Keywords: audit delay, firm size, DER, auditor opinion, and a public accounting firm size.